PENGARUH KOMUNIKASI ANTARPRIBADI TERHADAP KONSEP DIRI JULIANTO EKA PUTRA - Rohmawati S, Cindy Imelda; Rochim, Achluddin Ibnu; Yulianti, Tri (Universitas 17 Agustus 1945 Surabaya, 2018)
Success is not only desired and owned by people who are able, but those who cannot afford,even want to have it. For someone who is born from unrich people, having success thing is a pricelesshappiness. It is felt by Julianto Eka Putra who is growing in a regular neighborhood. Julianto EkaPutra initiated and motivated to make the VISION 2010 program with the aim is to establish freeschool and a charitable foundation that dedicated himself to help orphans in Indonesia who cannotafford to continue their study to high school education. The purpose of this study is to determine theeffect of Julianto Eka Putra’s self-concept on the students of Selamat Pagi Indonesia’s High SchoolBatu-Malang. The result of the first hypothesis reads the suspect classification and purpose of theinterpersonal communication affects the self-concept, is acceptable because of the calculation it tcount (1,944) > t table (1,667), second hypothesis is assumed to be accepted because of theeffectiveness of interpersonal communication is known that t count (4,335) > t table (1,667), thismeans that the independent variable X1 (classification and interpersonal communication objective)and X2 (interpersonal communication effectiveness) significantly affects the self concept of JuliantoEka Putra.Keywords: Classification and Interpersonal Communication Objective, Interpersonal CommunicationEffectiveness, Self Concept